Speculative activity, monetary policy and commodity prices - Yao, Wei; Alexiou, Constantinos (Cranfield University, 2019)
The dataset consists of key macroeconomic indicators sourced from the OECD and the FRED. Data on the thirteen commodities, which are classified as energy commodities (crude oil and heating oil), precious metal commodities (gold, silver, platinum, palladium and copper), agricultural commodities (wheat, sugar, soybeans, coffee and cocoa) or textile commodities (cotton) are not included in these dataset as they are not publicly available and restrictions apply. All data are monthly and span the period 1986:1 to 2018:7.
Keywords: 'commodity prices'; 'Monetary policy transmission'; 'Economics'; 'Time-Series Analysis'